К номенклатуре некоторых видов рода Cyclocoelum Brandеs, 1892 (Trematoda, Cyclocoelidae), паразитирующих у пастушковых и куликов - Искова, H.И. (Вестник зоологии, 1978)
Conclusions of Dubois (1959, 1965) and Macko (1965) that Cyclocoelum mutabile (Zeder) is the Rallidae parasite and C. obscurum (Leidy) — Charadriiformes parasite are confirmed. The pharynx of C. mutabile is 3 and more times as large as that of C. obscurum. A special attention is paid to this fact as it is one of the most constant characters when determining Cyclocoelum (Cyclocoelum) species. Tables of main morphological characters of the mentioned species are presented.